Effect of alkali and enzymatic treatments of banana fibre on properties of banana/polypropylene composites. (March 2018) - Vishnu Vardhini, KJ; Murugan, R; Surjit, R
Banana fibres are among the natural fibres obtained from the waste pseudostem of the banana plant, which can be used as reinforcement in the manufacture of thermoplastic composites due to its high specific strength compared to that of glass fibres and are sustainable alternatives. To improve the adhesion of natural fibres with the matrix material, the surface is usually modified using alkali. Surface modifications can also be done through eco-friendly enzymatic treatments. In this work, banana fibres were treated with alkali, laccase and xylanase enzymes at various treatment concentrations separately to modify the surface. Banana/polypropylene needle punched nonwovens were produced from each of these treated fibres and polypropylene fibres separately. Banana/polypropylene composites have been produced from these nonwovens using compression moulding technique and properties such as volume fractions, hardness, tensile strength, scanning electron microscope analysis, flexural strength and impact resistance were determined for all the composite samples. The densities and the void contents of these developed composites ranged between the range of 1.038–1.043 and 2.2% to 3.6%, respectively. The various treatments have increased the hardness by 8–21%, tensile strength by 24–69% with the highest for 20% xylanase enzyme treatment. The scanning electron microscope analysis of the tensile test samples also aids the tensile test results. The 100% polypropylene had a flexural strength of 25.43 MPa and that for banana fibre reinforced composites the improvements was in the range of 42 to 80%. Impact strength also showed similar trend as tensile with a highest impact strength of 120% for 20% xylanase enzyme treatment.